Melawan Tradisi Strategi Konvensional: Analisis Peningkatan Hasil Belajar Fikih dengan Strategi True or False - Azis, Abdul; Jannah, Fathul; Nasution, Umy Fitriani (Fitrah: Journal of Islamic Education, 2023)
Student learning outcomes often experience a decline, one of which is due to the lack of varied learning strategies. in this regard, this study aims to analyze the learning process carried out by the teacher and also student participation in the application of true or false learning strategies in Jurisprudence subjects in class VIII C MTs. Negeri 2 Labuhanbatu Utara. The research method used is Classroom action research consisting of two cycles. The main data source is the fiqh teacher in class VIII C MTs. Negeri 2 Labuhanbatu Utara and also students of class VIII C. Data collection techniques use observation sheets, tests, and documentation. The results revealed that learning fiqh using the True or False learning strategy can improve student learning outcomes. The increase in student learning can be seen from Cycle II which is the result of the application of this true or false learning strategy, which is 81.46% of the 48% percentage of the final result. So it can be said that this strategy provides an increase in student learning outcomes. This strategy is also responded well by students because it gives a pleasant impression. The implication of this research is a reference for fiqh teachers or Islamic religious education subject teachers in improving student learning outcomes.